Effective Approach towards Development of Idea through Foundations to Product Design - Alok, Govil; Anushalini, T.; Condoor, Sridhar (Journal of Engineering Education Transformations, 2018)
Nowadays, uniqueness, innovation, and team workers are expected in every aspect of industries. Every student undergoes a challenging task in the daytoday life to meet their long term and short term goal. Being proactive and exhibiting their skills acquires a job to make their dream come true. To enhance the design attributes, out of box thinking, creativity, teamwork, decision making this novice course named "Foundation to product design" inspires and motivates students to work in teams, to build prototypes, promotes learning and thinking skills, understands the role of the user and also improvises communication skills. These features formthe base to build their career of each individual to dwell in their professional life to become a successful or effectual engineer.